THE INFLUENCE OF MIGRATION PROCESSES ON PUBLIC CONSCIOUSNESS IN THE CONTEXT OF GLOBALIZATION: SOCIO-PHILOSOPHICAL ANALYSIS (Modern American Journal of Social Sciences and Humanities, 2026)
This article analyzes from a socio-philosophical point of view the impact on social consciousness of the phenomenon of migration, which is manifested as an integral component of the globalization process.his article analyzes from a socio-philosophical point of view the impact on social consciousness of the phenomenon of migration, which is manifested as an integral component of the globalization process. Migration is justifie. The article highlights the role of migration in the transformation of social consciousness, dialectical relations between national and global consciousness, as well as the socio-philosophical consequences of migration on the example of the Uzbek society.he article highlights the role of migration in the transformation of social consciousness, dialect.